PEDOT:PSS/Graphene Nanocomposite Hole-Injection Layer in Polymer Light-Emitting Diodes - Chun-Hsuan Lin; Kun-Tso Chen; Jeng-Rong Ho; J.-W. John Cheng; Raymond Chien-Chao Tsiang (Journal of Nanotechnology, 2012)
We report on effects of doping graphene in poly(3,4-ethylenedioxythiophene): poly(styrene sulfonate), PEDOT:PSS, as a PEDOT:PSS/graphene nanocomposite hole injection layer on the performance enhancement of polymer light-emitting diodes (PLEDs). Graphene oxides were first synthesized and then mixed in the PEDOT:PSS solution with specifically various amounts. Graphenes were reduced in the PEDOT:PSS matrix through thermal reduction. PLED devices with hole-injection nanocomposite layer containing particular doping concentration were fabricated, and the influence of doping concentration on device performance was examined by systematically characterizations of various device properties. Through the graphene doping, the resistance in the hole-injection layer and the turn-on voltage could be effectively reduced that benefited the injection and transport of holes and resulted in a higher overall efficiency. The conductivity of the hole-injection layer was monotonically increased with the increase of doping concentration, performance indices from various aspects, however, did not show the same dependence because faster injected holes might alter not only the balance of holes and electrons but also their combination locations in the light-emitting layer. Results show that optimal doping concentration was the case with 0.03 wt% of graphene oxide.